Biology : a curriculum guide for Newfoundland schools, grades X, XI - Newfoundland and Labrador. Department of Education. Division of Curriculum. (Government of Newfoundland and Labrador, Department of Education, Division of Curriculum, 1965)
Biology A curriculum Guide - Grades X, XI